Translating evolutionary history and protein-focused machine learning supports increased prevalence of hereditary haemorrhagic telangiectasia, one of the most common inherited disorders - Adriana Macko; Jill Pecon-Slattery; Claire L Shovlin (QJM: An International Journal of Medicine, 2026)
Abstract Background Recent genetic data suggest hereditary haemorrhagic telangiectasia (HHT) is 2-12 times more common than the clinically-ascertained prevalence, potentially above the ‘rare disease’ designation threshold, and undermining clinical predictions for asymptomatic individuals diagnosed by genetic testing. Aim To test, we examined if missense variants in HHT disease-causing genes may have been misclassified as pathogenic (LP/P) or benign (B/LB). Design Evaluation of ClinVar-annotated missense variants in ENG, ACVRL1 and SMAD4. Methods Human-independent methods using CodeXome for pan-primate evolutionary history, and AlphaMissense which incorporates AlphaFold predictions for protein misfolding were used to validate/reclassify pathogenic and benign missense variants Results ClinVar annotations were commonly conservative with 35-90% of rare missense substitutions in ENG, ACVRL1 and SMAD4 classified as variants of uncertain significance (VUS). CodeXome identified 92% of ClinVar-annotated B/LB variants were shared with other primate species, supporting their benign classification. AlphaMissense metrics strongly correlated with CodeXome, and 380/403 (94.3%) variants matched ClinVar benign-pathogenic annotations. However, a small number of variants showed conflicting classifications with ClinVar: 19/293 (6.5%) appeared to be over-called as LP/P by ClinVar representing 15/408 (3.7%) of genotyped families at Imperial, while 4/110 (3.6%) were apparently under-called as B/LB, and not accessible through clinical gene test reports. Newer pathobiological understanding of variants, and recognition of shared familial tendencies reflecting non-HHT heritable burdens were identified as possible explanations of over-calls. Conclusions Our findings suggest tools to simplify variant pathogenicity predictions; molecular diagnoses to revisit for HHT families, but do not materially influence prevalence estimates for ‘genetic’ HHT, challenging current clinical policies, training and standards.